Handbook of Occupational Health Psychology. 2003
DOI: 10.1037/10474-012
|View full text |Cite
|
Sign up to set email alerts
|

Job-related burnout: A review.

Abstract: This review focuses on the conceptual meaning of burnout and on some of the major antecedents, symptoms, and consequences of burnout in work organizations. Burnout is viewed as an affective reaction to ongoing stress whose core content is the gradual depletion over time of individuals' intrinsic energetic resources, including the expression of emotional exhaustion, physical fatigue, and cognitive weariness (Shirom, 1989). The review starts with a critical analysis of the major conceptual approaches to burnout.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
290
0
34

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 391 publications
(351 citation statements)
references
References 51 publications
(86 reference statements)
7
290
0
34
Order By: Relevance
“…Burnout is a multifaceted emotional syndrome of exhaustion, representing chronic reactions and negative affective response to prolonged stress at work (Maslach, Schaufeli, & Leiter, 2001;Shirom, 2003). In a rare longitudinal three-wave study, Demerouti et al (2009) found that exhaustion had a reciprocal relation with presenteeism in a sample of Dutch nurses.…”
Section: Hypothesis 3amentioning
confidence: 99%
“…Burnout is a multifaceted emotional syndrome of exhaustion, representing chronic reactions and negative affective response to prolonged stress at work (Maslach, Schaufeli, & Leiter, 2001;Shirom, 2003). In a rare longitudinal three-wave study, Demerouti et al (2009) found that exhaustion had a reciprocal relation with presenteeism in a sample of Dutch nurses.…”
Section: Hypothesis 3amentioning
confidence: 99%
“…This 12-item questionnaire evaluates three burnout dimensions: physical fatigue (PF) (4 items, e.g., "I feel physically drained"), emotional exhaustion (EE) (4 items, e.g., "I feel emotionally burned out at work") and cognitive weariness (CW) (4 items, e.g., "I have difficulty thinking about complex things"). Responses are rated on a 7-point Likert scale, ranging from 1 for never to 7 for always (Melamed, et al, 1999;Shirom, 2003).…”
Section: Instrumentsmentioning
confidence: 99%
“…Job burnout is a state of chronic emotional state including three components of cognitive, physical and emotional fatigue [5]. Job burnout could be defined as a consequence of chronic reduction of one's ability resources arising from long-term exposure to stress, especially job stressors.…”
Section: Introductionmentioning
confidence: 99%